Value of the Ratio of Occluder Versus Atrial Septal Length for Predicting Arrhythmia Occurrence after Transcatheter Closure in Children with Ostium Secundum Atrial Septal Defect - Mei Jin (Chinese Medical Journal, 2015)
Background: Transcatheter occlusion has been applied to treat ostium secundum atrial septal defect (OS ASD) since 1997. During the clinical practice, several postoperative complications including arrhythmia have been reported. This study aimed to evaluate the value of the ratio of atrial septal occluder (ASO) versus atrial septal length (ASL) for predicting arrhythmia occurrence after transcatheter closure in children with OS ASD. Methods: Six hundred and fifty-one children diagnosed with OS ASD underwent occlusion procedures after completing routine examinations. The onsets and types of arrhythmia both during and after the occlusion procedures were monitored. Treatments were given based on the individual types of arrhythmia. The binary logistic regression analysis and receiver-operating characteristic (ROC) curve were used in the analysis of value of the ratio of ASO/ASL for predicting postoperative arrhythmia occurrence. Results: Transcather occlusions were conducted in 651 children, among whom 7 children had different types and degrees of arrhythmia, with an incidence of 1.1%. The types of arrhythmia included sinus bradycardia, atrial premature beats, bundle branch block, and different degrees of atrioventricular block. Normal electrocardiograph findings were resumed in these 7 patients following active therapies such as corticoids, nutrition, and surgeries. The binary logistic regression and ROC analysis suggested that the ratio of ASO/ASL exhibited an intermediate predictive value for predicting arrhythmia occurrence after occlusion procedures. A cut-off value of 0.576 in the ratio provided a sensitivity of 87.5% and a specificity of 76.2% with an area under the ROC curve of 0.791 (95% confidence intervals, 0.655-0.926; P < 0.05) in predicting arrhythmia occurrence after the closure procedures. Conclusions: The ratio of ASO/ASL might be a useful index for predicting arrhythmia occurrence after closure procedures in children with OS ASD.